NON-VERBAL BEHAVIOR AS AN ELEMENT OF COMMUNICATIVE COMPETENCE OF A FUTURE TEACHER OF ECONOMICS (Pedagogy of Higher and Secondary Education, 2022)
The paper discloses the essence of nonverbal behavior and ways of its formation in the learning process of higher education.
Keywords: nonverbal behaviour; communications; competence.